Police-reported suicides during the first 16 months of the COVID-19 pandemic in Ecuador: A time-series analysis of trends and risk factors until June 2021 - Rebekka M. Gerstner; Freddy Narváez; Stuart Leske; M. Isabela Troya; Pablo Analuisa-Aguilar; Matthew J. Spittal; David Gunnell (The Lancet Regional Health. Americas, 2022)
Summary: Background: There are widespread concerns that the COVID-19 pandemic may increase suicides. Few studies have analysed effects beyond the pandemic's early months or examined changes in known suicide risk factors. Methods: Using time series models fit with Poisson regression, we analysed monthly police-reported suicides in Ecuador from January 2015 to June 2021. Treating March 2020 as the start of the pandemic, we calculated rate ratios (RRs) comparing the observed to the expected number of suicides for the total population and by age and sex groups. We investigated changes in risk factors, precipitants, geographic distribution, and suicide methods. Findings: There was no evidence that suicide rates were higher than expected during the pandemic (RR 0·97 [95% CI 0·92–1·02]). There was some evidence of fewer than expected male suicides (RR 0·95 [95% CI 0·90–1·00]). The proportion of suicides occurring in urban and coastal areas increased but decreased amongst indigenous and other minorities. The proportions of suicides with evidence of alcohol consumption, disability, and amongst married and cohabiting individuals decreased, whereas suicides where mental health problems were considered contributory increased. There were relative increases in the proportion of suicides by hanging but decreases in self-poisoning and other suicide methods. Interpretation: The pandemic did not appear to adversely impact overall suicide numbers nationwide during the first 16 months of the pandemic. Reduced alcohol consumption may have contributed to the decline in male suicides. Funding: None.